2012
DOI: 10.1097/rlu.0b013e31823924bb
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between GLUT-1 and Vascular Endothelial Growth Factor Expression and 18F-FDG Uptake in Esophageal Squamous Cell Cancer Patients

Abstract: (18)F-FDG uptake can be determined by GLUT-1 and VEGF. SUV(max) would have a connection with the tumor progression and lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Increased glucose uptake is an acknowledged characteristic of cancer cells, and applying this feature when imaging tumors using radioactive tomography has become a diagnostic standard [18, 19]. However, no definite evidence distinguishes different types of glucose transporters that affect the glucose uptake from one another.…”
Section: Discussionmentioning
confidence: 99%
“…Increased glucose uptake is an acknowledged characteristic of cancer cells, and applying this feature when imaging tumors using radioactive tomography has become a diagnostic standard [18, 19]. However, no definite evidence distinguishes different types of glucose transporters that affect the glucose uptake from one another.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that GLUT1 has an important role in 18 F-FDG uptake in patients with lung cancer, soft tissue sarcoma and pancreatic cancer [9], [17], [18]. Conversely, Tohma et al reported low correlation between 18 F-FDG uptake and GLUT1 expression in esophageal cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies have focused on defining the relationship between FDG uptake and the expression of tumor biomarkers, including nuclear- associated antigen Ki-67, cyclooxygenase-2 (Cox-2), vascular endothelial growth factor (VEGF) and the glucose transporter 1 (GLUT1) in relation to lung cancer [4], [8], [9]. To date, these have reported a correlation between SUV max and tumor biomarkers and have contributed to understanding the Warburg effect and identifying tumor-related genes that are associated with the SUV, thereby providing a robust basis for staging, prognosis and personalized treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Increased glucose uptake is a well-known feature of cancer cells, and is widely used to image tumors using radioactively labeled glucose in positron emission tomography, which is, for example, part of the diagnostic standard in lung cancer [4,15]. The glucose uptake capacity of cells largely depends on the expression of glucose transporters, which transport glucose across membranes.…”
Section: Discussionmentioning
confidence: 99%